Penerapan Lean Six Sigma dalam Peningkatan Kinerja Produksi Spring Guide - Sansan Octavian; Endang Prasetyaningsih; Chaznin R. Muhammad (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. PT Gradien Manufaktur Indonesia is a manufacturing company that produces motorcycle shockbreker components using make-to-order (MTO) and engineering-to-order (ETO) strategies. Such systems demand high process efficiency and superior product quality. However, wastes in the form of waiting, defects, and excess inventory are still prevalent in the production process, resulting in suboptimal production performance. This research aims to identify dominant wastes, analyze root causes of the issues, and formulate improvement recommendations to enhance production performance. The methodology employed is Lean Six Sigma with the DMAIC (Define, Measure, Analyze, Improve, Control) approach. Analytical tools utilized include Value Stream Mapping (VSM), 7 Waste, VALSAT, and fishbone diagrams, along with performance measurements using Process Cycle Efficiency (PCE), Defects Per Million Opportunities (DPMO), and sigma levels. The results indicated an initial PCE of 64.33% and a DPMO of 3.215,22 with a sigma level of 4,225. Proposed improvements comprising preventive maintenance, process time standardization, and material flow control successfully increased the PCE to 72.23%, reduced the DPMO to 3,074.29, and improved the sigma level to 4,24. Abstrak. PT Gradien Manufaktur Indonesia merupakan perusahaan manufaktur yang memproduksi komponen shockbreker sepeda motor dengan stategi make-to-order dan engineering-to-order. Sistem ini menuntut efisiensi proses dan kualitas produk yang tinggi. Namun, dalam proses produksi masih ditemukan pemborosan berupa waiting, defect, dan excess inventory yang berdampak pada rendahnya kinerja produksi. Penelitian ini bertujuan untuk mengidentifikasi pemborosan dominan, menganalisis akar penyebab permasalahan, serta merumuskan usulan perbaikan guna meningkatkan kinerja produksi. Metode yang digunakan adalah Lean Six Sigma dengan pendekatan DMAIC (Define, Measure, Analyze, Improve, Control). Alat analisis meliputi Value Stream Mapping (VSM), 7 Waste, VALSAT, diagram fishbone, serta pengukuran kinerja menggunakan Process Cycle Efficiency (PCE), Defects Per Million Opportunities (DPMO), dan tingkat sigma. Hasil penelitian menunjukkan nilai PCE sebesar 64,33% dan DPMO sebesar 3.215,22 dengan tingkat sigma 4,225. Usulan perbaikan yang diberikan berupa preventive maintenance, standarisasi waktu proses, dan pengendalian aliran material mampu meningkatkan PCE menjadi 72,23%, menurunkan DPMO menjadi 3.074,29, serta meningkatkan tingkat sigma menjadi 4,24.